Customers' perceived value and dining choice through mobile apps in Indonesia. Issue 1 (26th February 2020) - Shah, Adnan Muhammad; Yan, Xiangbin; Shah, Syed Asad Ali; Ali, Mudassar
Abstract : Purpose: The latest mobile technology may shape consumers' motivations by allowing them to order a variety of foods using smartphone apps. Following the stimulus–organism–response (SOR) framework and using a mixed methods approach, this study investigates the impacts of different components of mobile dining on customers' perceived value, which leads to actual purchase intentions. Furthermore, this study examines the moderating effect of the restaurant type. Design/methodology/approach: Data were collected via an online questionnaire survey from 351 individuals in the city of Jakarta (Indonesia) who actually used mobile apps to order food online. Data analysis was carried out using structural equation modeling. Findings: The findings reveal that source credibility, review valence, the navigation system, food quality and service quality significantly impact customers' perceived value. Customers' perceived value, in turn, positively affects their purchase intentions. The findings also reveal that the impacts of review valence, the navigation system, food quality and service quality on customers' perceived value depend on the different levels of restaurants. Originality/value: This study is among the first in the mobile commerce research that studies the impacts of mobile electronic word-of-mouth (eWOM), system quality and overall restaurant image on dining choices by considering actual mobile shoppers. Second, this study extends the SOR model to examine the impact of the mobile environment-based characteristics on the perceived value that leads to purchase intentions. Third, the current study examines whether the relationships that are discussed early on differ based on the restaurant type. The findings of this study could help practitioners achieve a deeper understanding of diners' behaviors due to the perceived benefits of mobile dining.